Dampak Penggunaan Layanan Pinjaman Online dan Perlindungan Hukum Terhadap Konsumen - Prayuti, Yuyut; Syifa, Hilda Ainis; ZA, Nanang Fahruddin (Universitas Muhammadiyah Ponorogo, 2025)
Online loans are financial institutions that provide loans and borrowing of funds through digital technology. This study aims to examine the impact of using online loan services and the legal protection applied to online loan consumers. This study uses a normative legal method with a qualitative approach. The data used are secondary data obtained from laws and regulations, legal doctrine, related literature, and jurisprudence. Data collection techniques are carried out through document studies, while data analysis is carried out qualitatively by interpreting and connecting relevant legal data to examine legal protection for online loan consumers. The results of this study indicate that the use of online loans by consumers has positive and negative impacts. One of the positive impacts is providing significant economic development for the community and the negative impact is high interest rates. Legal protection for online loan consumers is regulated in the Financial Services Authority Regulation (POJK) Number 2 of 2023 which includes protection of assets, privacy, and consumer data; obligations and prohibitions for consumers and online loan actors; collection mechanisms carried out by online loan actors to consumers; and so on.